1999
DOI: 10.3141/1681-01
|View full text |Cite
|
Sign up to set email alerts
|

Use of Reclaimed Asphalt Pavement in Superpave Hot-Mix Asphalt Applications

Abstract: Implementation of the Superpave mix design method has encouraged the use of coarser hot-mix asphalt (HMA) mixtures, which require tight control of both the overall gradation and the percent passing the 0.075-mm (No. 200) screen. There is some concern that use of reclaimed asphalt pavement (RAP) in Superpave mixtures may be seriously limited because stockpiles of RAP may have widely variable gradations as well as high percentages of minus 0.075-mm material. The possibility of splitting RAP stockpiles by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Meanwhile, the properties of aged binder on the RAP aggregates determine the properties of virgin asphalt that needs to be added to new mixtures containing RAP [10]. Based on the requirements of binder property in new HMA mixture, the property of virgin asphalt and the content limit of RAP used in the mixture could be estimated.…”
Section: Hypothesis and Research Methodologymentioning
confidence: 99%
“…Meanwhile, the properties of aged binder on the RAP aggregates determine the properties of virgin asphalt that needs to be added to new mixtures containing RAP [10]. Based on the requirements of binder property in new HMA mixture, the property of virgin asphalt and the content limit of RAP used in the mixture could be estimated.…”
Section: Hypothesis and Research Methodologymentioning
confidence: 99%
“…Gardiner [17] concluded that the complex modulus is not solely controlled by the stiffness of the binder, whereas several other factors including the gradation and angularity of the aggregate have impact on it. Mixing method, heating temperature, and mixing duration of RAP need to be optimized to ensure the complete blending of the old and new binders so that the plant production process can be better simulated in the lab [18].…”
Section: Effect Of Rap Particle Size On Binder-blending Phenomenonmentioning
confidence: 99%
“…The most commonly used method of testing the RAP binder properties is done by extracting and recovering asphalt binder with solvents (AASHTO T164 /ASTM D 2172) [7,8] . However, the use of solvents is expected to alter the binder properties, and the procedure results are highly variable [9][10][11][12][13] . These issues are shown to limit the use of RAP in highway pavements and are resulting in requiring unnecessary barrier s for effective use of quality RAP materials in construction.…”
Section: Introductionmentioning
confidence: 99%